IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS BUDAYA RELIGIUS - Aris Sahruli; Rohmad Widodo; Budiono Budiono (University of Muhammadiyah Malang, 2017)
This research was conducted at SMP Muhammadiyah 2 Batu, with the aim of (1) to fnd out and describe the implementation of character education based on religious culture in SMP Muhammadiyah 2 Batu; (2) to fnd out and describe the enabling and inhibiting factors in the implementation of character education based on religious culture in SMP Muhammadiyah 2 Batu; (3) to describe the solutions taken in addressing the problems that arise in the implementation of character education based on religious culture in SMP Muhammadiyah2 Batu.This study uses qualitative research techniques. Where researchers plunge directly to obtain information related to the title of this research. The collection of data obtained from interview techniques, observation, and documentation. The informant that needs to be explored include, the principal of SMP Muhammadiyah 2 Batu, vice of the student , vice of sarpras, PPKn teachers, religious teachers, and students of class VII, VIII, and IX. Then the data were analyzed by descriptive qualitative. The results showed that the implementation of character education based on religious culture in SMP Muhammadiyah 2 Batu, implemented through collaboration between the KTSP curriculum with the curriculum of Primary and Secondary Education Muhammadiyah assemblies and their development become specifc policies that have been agreed upon by the school. The development is carried out through habituation or cultural activities in schools are routinely carried out, namely: Culture 5S, Kultum and Duha prayer, Quranic Literacy (BTA), afternoon prayers in congregation , Fridayprayers, empathy (caring), study end-run council/IPM, and the Great Day of Islam (PHBI). Religious culture based on character education is very important in shaping the character and morals of students that possess akhlakul karimah corresponding to 18 values rooted in religious character, Pancasila, cultural, and educational purposes. Supporting factors in the implementation of character education based on religious culture in SMP Muhammadiyah 2 Batu is a curriculum, agreements, teachers (human resource) that support, facilities andinfrastructure (Mosque) in the school, the program, control of community (community participation). Inhibiting factor is student input that are heterogeneous and plural so it can not evenly distributed, the external factors (social environment or community), the limitations of the existing facilities at the school, the programs are less agreed, student awareness is still low. The solution is the school needs to improve, and always keep the communication and cooperation with parents, provide insight to the child, parents, and related institutions, develop and optimizing potentials, as well as tighter regulations in the character formation of students.